PERAN PENULIS NASKAH DAN AKTOR DALAM FILM FIKSI " IMPIAN TERTULIS " - Ginanda Rezza Fatahillah (2024)
The fictional film "Impian Tertulis" discusses the life of a disabled person who dreams of becoming a writer. This film contains many elements of literacy and motivation in achieving your dreams. The aim of this film is to increase understanding of the importance of respecting fellow humans and that every human being has the same opportunity to achieve their dreams. This film reveals that in life, humans have equality regardless of shortcomings. Scriptwriters have an important role in designing, creating and developing interesting plots or concepts. So that the message raised in this film can be conveyed clearly and precisely. Overall, this fiction film briefly and clearly conveys a message about the importance of a strong sense of desire in achieving dreams, even though there are many shortcomings and problems in the process.